Modified Adaptive Sliding Mode Control for Trajectory Tracking of Mini-drone Quadcopter Unmanned Aerial Vehicle - Jutarut Chaoraingern; Vittaya Tipsuwanporn; Arjin Numsomran (My University, 2020)
Unmanned Aerial Vehicles are among the most widely attracting interest, especially in the applications of transportation, inspection, and surveillance.The great mechanisms for motion control are set to become a vital factor in performing the robust and accurate stabilized flight relied on perturbations and disturbances.This paper presents modified adaptive sliding mode control for trajectory tracking of mini-drone quadcopter unmanned aerial vehicles, which aims at demonstrating the effectiveness of nonlinear adaptive control strategy for achieving the desired performance of the mini-drone quadcopter system.Besides providing mathematical modeling and nonlinear dynamic characteristic details of mini-drone quadcopter actuated system, the modified adaptive sliding mode algorithm is developed using adaptation law based on Lyapunov stability approach then applied on the attitude loop and the altitude loop control system so that the nonlinear adaptive behavior of the controller enables the compensation of disturbances and parameter perturbations.The effectiveness validations of the proposed control technique compared with the traditional approach are performed through the Matlab simulation.The results have been illustrated that the modified adaptive sliding mode control can decrease the error performance indexes to the minimum ISE at 1.041 m 2 and the zero percentage of overshoot while enables excellent stability and robustness even in the presence of parameter perturbations and disturbance.
Keywords: Quadcopter; Lyapunov stability; Robustness; Drone; Overshoot (microwave communication); Adaptive Control of Nonlinear Systems